Current Problems of Cadastral Valuation Reliability - V. Yu. Sutyagin; M. V. Bespalov (Учёт. Анализ. Аудит, 2018)
The article deals with the current issues of cadastral valuation reliability on the example of Tambov region. The authors consider the genesis of development of cadastral valuation institute and the related matters. The problems of cadastral valuation result from the imbalance of the taxation system because property and land taxes are a few real local taxes. That is why local authorities solve the problem of the development of the local tax base by means of systematic overestimating cadastral value. In article analyses certain problems of cadastral valuation, such as procedural aspects and statistics of contesting cadastral valuation, accounting and singling out of a value added tax in the fnal result of valuation along with the arising conﬂicts of interest between the regional and federal authorities.